Association between blood urea nitrogen to serum albumin ratio and in-hospital mortality of patients with sepsis in intensive care: A retrospective analysis of the fourth-generation Medical Information Mart for Intensive Care database - Cai, Shaoyan; Wang, Qinjia; Chen, Chao; Guo, Chunming; Zheng, Liangjie; Yuan, Min (Frontiers in Nutrition, 2022)
Background This study aimed to investigate the relationship between the blood urea nitrogen to serum albumin ratio (BAR) and in-hospital mortality in patients with sepsis. Materials and methods This is a retrospective cohort study. All septic patient data for the study were obtained from the intensive care unit of Beth Israel Deaconess Medical Center. Adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated using multivariable Cox regression analyses. Survival curves were plotted and subgroup analyses were stratified by relevant covariates. Results Among 23,901 patients, 13,464 with sepsis were included. The overall in-hospital mortality rate was 18.9% (2550/13464). After adjustment for confounding factors, patients in the highest BAR quartile had an increased risk of sepsis death than those in the lowest BAR quartile (HR: 1.42, 95% CI: 1.3–1.55), using BAR as a categorical variable. When BAR was presented as a continuous variable, the prevalence of in-hospital sepsis-related death increased by 8% (adjusted HR: 1.08, 95% CI: 1.07–1.1, P < 0.001) for each 5-unit increase in BAR, irrespective of confounders. Stratified analyses indicated age interactions (P < 0.001), and the correlation between BAR and the probability of dying due to sepsis was stable. Conclusion BAR was significantly associated with in-hospital mortality in intensive care patients with sepsis. A higher BAR in patients with sepsis is associated with a worse prognosis in the ICU in the USA. However, further research is required to confirm this finding.